ANTESEDEN KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - Putu Wenny Saitri; Ni Putu Yuria Mendra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This study aims to examine and obtain empirical evidence of the influence of the Independent Board of Commissioners, Institutional Ownership, Profit Quality, Capital Structure, Company Size, and Company Growth on Company Performance in Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange (IDX). The research population is manufacturing companies in the consumer goods industry sector which are listed on the IDX in 2019-2021. The sample in this study were 46 companies which were determined based on the purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression. The results of the study show that the independent board of commissioners has a positive effect on company performance. Institutional ownership has a positive effect on company performance. Earnings quality has no effect on company performance. Capital structure has a negative effect on company performance. Company size has a positive effect on company performance. The company's growth has no effect on the company's performance.